OpenSUSE 11.0 and SUSE Linux Enterprise Server bible - Whittaker, Roger, 1955- (Bible., 2008)
Presenting updated coverage of openSUSE 11.0 and SUSE Linux Enterprise Server 11.0, this reference is written by Novell insiders and boasts the most up-to-date information availableTopics covered include the openSUSE project, command line programs and implementing online services, virtualization, kernel updates, Enterprise Architecture, and moreReviews Linux fundamentals such as methodologies, partitions, and file system, and features a new section devoted entirely to end-user needsThe DVD includes the openSUSE 11.0.